DISCOVERING THE EFFECTIVENESS OF TEACHING METHODS IN TEACHING COMMUNICATIVE ARABIC AT SULTAN SHARIF ALI ISLAMIC UNIVERSITY: FACULTY OF ARABIC LANGUAGE AS CASE STUDY - Achmad Yani Bin Imam Subari,; Siti Sara Binti Haji Ahmad,; RafidahBinti Abdullah,; Hambali Bin Haji Jail,; RafizahBinti Abdullah,; NurBasirahBinti Haji Rosmin, (IJRDO- Journal of Educational Research, 2024)
This research aims to identify the effectiveness of the objectives of teaching communicative Arabic at the Faculty of Arabic Language at Sultan Sharif Ali Islamic University in the Sultanate of Brunei Darussalam. The researchers distributed the questionnaire to 14 first-year students from the Faculty of Arabic Language at Sultan Sharif Ali Islamic University who studied communicative Arabic course in the year 2024 AD, out of the 21 first-year students from the Faculty of Arabic Language at Sultan Sharif Ali Islamic University who studied Communicative Arabic course in 2024 AD. This sample represents 66% of all the students. After obtaining the data needed for this research, they analysed it quantitatively and evaluatively to obtain the required results. This research arrived at results showing that the positive aspects of teaching methods in teaching communicative Arabic at Sultan Sharif Ali Islamic University are evident in the fact that the teacher speaks Arabic when teaching communicative Arabic at Sultan Sharif Ali Islamic University, at a rate of 90%, and that he asked the students to engage in oral dialogue with each other in Arabic on topics related to daily communication, at a rate of 91.4%.He records the students’ voices when they communicate orally in the classroom at a rate of 64.3%, and corrects the oral errors that students made when they dialogue orally in the classroom by listening to their recorded voices, at a rate of 80%. And that students engage in written dialogue with each other in Arabic in the classroom at a rate of 87.1%, and that he displays what the students (or some of them) conducted in written dialogue on the screen in front of the class at a rate of 87.1%, and that he corrects written errors that occur from students (or some of them) on the screen through the projector in front of the class at a rate of 78.6%, and that he gives his students sufficient opportunity to listen to Arabic voices on topics related to daily communication at a rate of 82.9%.He gives students adequate opportunity to read Arabic dialogues on topics related to daily communication at a rate of 88.6%, and gives students adequate opportunity to engage in oral dialogue among themselves on topics related to daily communication at a rate of 87.1%, and gives students opportunity to sufficiently write dialogue on topics related to daily communication at a percentage of 84.3%, and that he uses the attractive method in the communicative Arabic language course at a rate of of 88.6%, and that he uses various teaching methods in the communicative Arabic language course at a rate of 87.1%, and he trains students in the four language skills at a balanced rate 87.1%. The negative side appears in the fact that teacher does not speaking Arabic when teaching communicative Arabic at a rate of 10%. And that Students are not required to engage in oral dialogue in Arabic on topics related to daily communication, at a rate of 8.6%, and students’ voices are not recorded when they engage in oral dialogue in the classroom at a rate of 35.7%.and that he does not correct the oral errors made by students when they engage in an oral dialogue in the classroom by listening to their recorded voices, at a rate of 20%, and that he does not ask students to engage in written dialogue with one another in Arabic in the classroom at a rate of 12.9%, and that he does not display the written dialogue conducted by the students (or some of them) on the screen in front of the class, at a rate of 12.9%, and that he does not correct the written errors made by the students (or some of them) on the screen through the projector in front of the class at a rate of 21.4%, and he does not give students enough opportunity to listen to Arabic voices on topics related to daily communication at a rate of 17.1% and that he does not give students enough opportunity to read Arabic dialogues on topics related to daily communication at a rate of 11.4%. He does not give students enough opportunity to engage in oral dialogues with one another about topics related to daily communication, at a rate of 12.9%, and does not give students enough opportunity to write dialogues about topics related to daily communication at a rate of 15.7%. He uses the attractive method in the communicative Arabic language subject at a rate of 11.4%, and he does not use diverse teaching methods in the communicative Arabic language course rate of 12.9%, and he does not train students in the four language skills at a balanced percentage, at a rate of 12.9%.